KARAKTERISASI SENSOR HALL EFFECT SEBAGAI SENSOR MAGNETIK PADA PROTOTIPE PENJELAJAH PENGUKUR MEDAN MAGNET DENGAN SISTEM KENDALI ANDROID - Hidayatie, Nadya; Indrasari, Widyaningrum; Umiatin, Umiatin (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2017)
The prototype explorer is a device that can work measuring the magnetic field of the magnetic material that spread at desired location. The main component of the prototype is the Hall Effect UGN3503 magnetic sensor. Characterization of magnetic sensor has been performed by using coil calibration and Gaussmeter type IDR-325. From the characterization known the result that the value of sensitivity the sensor equal to 595 G/V with relative error 2,55 %. The sensor can work effectively to detect a weak magnetic field of 0,1068 G at a distance of 5 cm. Keywords: Hall Effect, Robot Explorer, Android Application